Impact of an endorectal coil for 1H-magnetic resonance spectroscopy of the prostate at 3.0 T in comparison to 1.5 T: Do we need an endorectal coil?. Issue 8 (August 2016) - Hoffner, Maximilian K.M.; Huebner, Frank; Scholtz, Jan Erik; Zangos, Stephan; Schulz, Boris; Luboldt, Wolfgang; Vogl, Thomas J.; Bodelle, Boris
Abstract: Objectives: To evaluate the influence of endorectal coil (ERC) regarding spectral quality and diagnostic suitability and diagnostic performance in 3.0 T 1H-magnetic resonance spectroscopy imaging (MRSI) compared to 1.5 T MRSI. Materials and methods: The study was approved by the Institutional Review Board. MRSI of the prostate was performed on 19 patients at 1.5 T with ERC (protocol 1), at 3.0 T with a disabled ERC (protocol 2) and at 3.0 T with ERC (protocol 3). Age, weight, body size, body-mass-index, prostate volume, time between measurements, diagnostic suitability of spectra, histopathological results after biopsy of cancer suspect lesions (CSL), sensitivity and specificity were evaluated. Signal-to-noise ratio (SNR) was calculated and compared using semiparametrical multiple Conover-comparisons. Correlations between SNR and prostate volume and BMI were indicated using Pearson correlation coefficient. Distribution of SNR was evaluated for prostate quadrants. Results: Diagnostic suitable spectra were achieved in 76 % (protocol 1, 100% in CSL), 32 % (protocol 2, 59% in CSL) and 50 % (protocol 3, 80% in CSL) of the voxels. SNR was significantly higher in protocol 3 compared to protocol 2 and 1 (93, 729 vs. 27, 836 vs. 32, 897, p < 0.0001) with significant difference between protocol 2 and 1 (p < 0.023). Highest SNR was achieved in the dorsal prostate (protocols 1 and 3; p < 0.0001). Sensitivity at 3.0 T was higher with use of ERC. Specificity was highest at 1.5 T with ERC. Conclusion: The ERC improves the diagnostic suitability and the SNR in MRSI at 3.0 T. Less voxels at 3.0 T with disabled ERC are suitable for diagnosis compared to 1.5 T with ERC. MRSI at 3.0 T with ERC shows the highest SNR. SNR in dorsal quadrants of the prostate was higher using ERC.